Basic Beliefs, the Embryo Rescue Case, and Single-Issue Voting: A Response to Dustin Crummett - McNabb, Tyler; DeVito, Michael (The National Catholic Bioethics Quarterly, 2021)
In this essay, we respond to Dustin Crummett’s argument that one cannot consistently appeal to body count reasoning to justify being a single-issue pro-life voter if one is also committed to the usual response to the embryo rescue case. Specifically, we argue that a modified version of BCR we call BCR* is consistent with the usual response. We then move to address concerns about the relevance of BCR* to Crummett’s original thesis.

Cognitive Science of Religion and Classical Theism: A Synthesis - McNabb, Tyler Dalton; DeVito, Michael (Religions, 2022)
Launonen and Mullins argue that if Classical Theism is true, human cognition is likely not theism-tracking, at least, given what we know from cognitive science of religion. In this essay, we develop a model for how classical theists can make sense of the findings from cognitive science, without abandoning their Classical Theist commitments. We also provide an argument for how our model aligns well with the Christian doctrine of general revelation.

Divine foreknowledge and human free will: Embracing the paradox - DeVito, Michael; McNabb, Tyler Dalton (International Journal for Philosophy of Religion, 2021)

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)

Houston, Do We Have a Problem?: Extraterrestrial Intelligent Life and Christian Belief - McIntosh, C. A.; McNabb, Tyler Dalton (Philosophia Christi, 2021)
Would the existence of extraterrestrial intelligent life (ETI) conflict in any way with Christian belief? We identify six areas of potential conflict. If there be no conflict in any of these areas—and we argue ultimately there is not—we are confident in declaring that there is no conflict, period. This conclusion underwrites the integrity of theological explorations into the existence of ETI, which has become a topic of increasing interest among theologians in recent years.

Mary and Fátima: A Modest C-Inductive Argument for Catholicism - Mcnabb, Tyler Dalton; Blado, Joseph E. (Perichoresis, 2020)
AbstractC-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.

Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity - McNabb, Tyler; DeVito, Michael (New Blackfriars, 2022)

Papal Bull: A Response to Contemporary Papal Scholarship - McNabb, Tyler Dalton (Journal of Biblical and Theological Studies, 2021)

Pestilent Popes or a Pestilent Church? Judaism, Catholicism, and Skeptical Theism - McNabb, Tyler Dalton (The Heythrop Journal, 2020)

The evolutionary argument against naturalism: a Wittgensteinian response - DeVito, Michael; McNabb, Tyler (International Journal for Philosophy of Religion, 2022)
In this essay, we put forth a novel solution to Plantinga’s Evolutionary Argument Against Naturalism, utilizing recent work done by Duncan Pritchard on radical skepticism. Key to the success of Plantinga’s argument is the doubting of the reliability of one’s cognitive faculties. We argue (viz. Pritchard and Wittgenstein) that the reliability of one’s cognitive faculties constitutes a hinge commitment, thus is exempt from rational evaluation. In turn, the naturalist who endorses hinge epistemology can deny the key premise in Plantinga’s argument and avoid the dilemma posed on belief in the conjunction of naturalism and evolution.